1995
DOI: 10.1007/bf01700657
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of partial liquid ventilation with perfluorocarbon in acute lung injury

Abstract: Objective: To assess the effect of partial liquid ventilation with perfluorocarbons on hemodynamics and gas exchange in large pigs with induced acute lung injury (ALI). Design: Randomized, prospective, double-control, experimental study. Setting: Experimental intensive care unit of a university. Materials: Eighteen large pigs (50 _+ 5 kg body weight) with an average anterior posterior thoracic diameter of 24 cm and induced acute lung injury. Interventions: All animals were surfactant depleted by lung lavage to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 17 publications
3
35
0
1
Order By: Relevance
“…The improvements in pulmonary mechanics might have further improved gas exchange during PLV in our study. Our results confirmed that there were no significant effects on systemic circulation by PLV, and these results were also compatible with previous studies (8,24). However, regarding pulmonary circulation, PLV decreased PAP significantly.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The improvements in pulmonary mechanics might have further improved gas exchange during PLV in our study. Our results confirmed that there were no significant effects on systemic circulation by PLV, and these results were also compatible with previous studies (8,24). However, regarding pulmonary circulation, PLV decreased PAP significantly.…”
Section: Discussionsupporting
confidence: 93%
“…Because of its high density and low surface tension, perfluorocarbon recruits the atelectatic lung region. A number of animal studies reported an improvement in gas exchange with this technique (2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…However, a filling volume of 30 mL/kg of PFOB was shown to be more effective than 15 mL/kg in preterm lambs (31). After intratracheal administration of 5-25 mL/kg of liquid PFOB in 5-mL/kg doses, PaO 2 was significantly different from the control group only after administration of 15-25 mL/kg in adult pigs (32). In neonatal piglets, PLV with a filling volume of full residual capacity was more effective than a volume of half residual capacity in a bypass model (33).…”
mentioning
confidence: 85%
“…PLV is another approach to improve oxygenation, ventilation, lung mechanics, and histologic changes in critically impaired lungs (7)(8)(9)(10)(11)(12). PFCs are excellent solvents for carbon dioxide and oxygen and disperse easily because of their high spreading coefficient, recruiting collapsed alveoli.…”
mentioning
confidence: 99%